Social acceptance and economic impacts of biomethane: A resource for energy sustainability - Idiano D'Adamo; Francesco Ferella; Matteo Fuoco; Massimo Gastaldi (Sustainable Production and Consumption, 2025)

A Case of Anti-Ma2 Encephalitis Presenting with Pendular Torsional Nystagmus - Gloria Vaghi; Elisa Vegezzi; Paola Bini; Matteo Gastaldi; Luca Diamanti; Enrico Marchioni; Silvia Colnaghi (The Cerebellum, 2023)
Antibodies against the neuronal protein Ma2 have been reported in a peculiar form of paraneoplastic encephalitis with prominent involvement of the limbic, brainstem, and diencephalic structures and usually associated with germ cell testicular, lung, or breast cancer. The diagnosis is frequently challenged by atypical clinical manifestations including parkinsonism, sleep disturbances, hypothalamic-pituitary dysfunctions, and motor neuron-like syndrome. In recent years, the advent of monoclonal antibodies targeting immune checkpoints has deeply changed the treatment of different tumors, especially melanoma and lung cancer. However, given their nature, an increasing number of neurological immune-related adverse events, including ocular motor abnormalities, have been described. Here, we report a woman with advanced non-small cell lung cancer treated with anti-PD-L1 durvalumab, presenting with an isolated pendular torsional nystagmus, in association with anti-Ma2 antibodies. This peculiar case widens our knowledge on the clinical presentation of anti-Ma2 encephalitis associated with checkpoint inhibitors.

Acquisition of human immunodeficiency virus infection in a patient with multiple sclerosis: could these conditions positively influence each other’s course? - Ilaria Mainardi; Maria Teresa Ferrò; Matteo Gastaldi; Diego Franciotta; Paola Cinque (Journal of NeuroVirology, 2020)

JC virus urinary excretion and seroprevalence in natalizumab-treated multiple sclerosis patients - Serena Delbue; Francesca Elia; Camilla Carloni; Valentina Pecchenini; Diego Franciotta; Matteo Gastaldi; Elena Colombo; Lucia Signorini; Silvia Carluccio; Anna Bellizzi; Roberto Bergamaschi; Pasquale Ferrante (Journal of NeuroVirology, 2015)